Electrochemical Synthesis of Titania Nanotubes in Glycerol-Choline Chloride Ionic Liquid for Photodegradation of Formaldehyde - SAHRIN, NURUL TASNIM (2021)
The present research aimed to develop a photocatalytic system based on TiO2 nanotubes (NTs) driven by visible light for the removal of formaldehyde (HCHO) which causes human health problem such as sick building syndrome. A series of TiO2 NTs were synthesized employing ionic liquid (IL) mediated electrochemical anodization method. The TiO2 NTs were grown on titanium foil in a mixture of glycerol and choline chloride (Gly-ChCl) ionic liquid as fluoride-free electrolyte. The IL was synthesized, and its physicochemical properties were determined using various characterization technique. The effect of various synthesis parameters including anodization voltage, anodization duration and calcination temperature on the physicochemical properties of TiO2 NTs and their performance for HCHO were investigated. The results revealed a significant impact of synthesis parameters on the properties of TiO2 NTs and HCHO removal. The anodization voltages of 20, 25 and 30 V for 60 min produced TiO2 NTs with well aligned tubular structure. However, increasing the voltage beyond 30 V led to the rupture, disintegration, and less dense distribution of the tubular structure of the TiO2 NTs. The calcination temperatures as low as 300°C (30 V) and 350°C (20 V) were able to successfully transform amorphous NTs to anatase crystalline phase. The tubular structure was distorted, severe pore rupture, and disintegration of the NTs surface was observed upon increasing the calcination temperature beyond 300°C. Both samples anodized at 20 and 30 V were characterized using Field Emission Scanning Electron Microscopy, X-ray Diffraction, Photoluminescence and X-ray Photoelectron Spectroscopy to determine their properties. Most importantly, the electron-hole recombination was considerably suppressed in the best performing NTs samples synthesized at 30 V for 60 min and calcined at 300°C for 120 min which showed the highest HCHO removal of 27.87 mgL-1g-1 within 120 min of visible light irradiation. The recyclability of the best performing photocatalyst showed a slight reduction from 27.87 mgL-1g-1 to 23.18 mgL-1g-1 and 20.35 mgL-1g-1 after three consecutive runs.